2000
DOI: 10.1111/j.1445-5994.2000.tb00835.x
|View full text |Cite
|
Sign up to set email alerts
|

Advance care planning in residential care

Abstract: Advanced directives are infrequently used in residential care. Further qualitative and quantitative studies are warranted to explore current processes of decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
39
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 19 publications
(1 reference statement)
5
39
3
Order By: Relevance
“…This paper presents the key findings of the pre-implementation evaluation; post-implementation changes to these findings will be reported in a future paper. We hypothesised that although pre-implementation ACP awareness and practice within the project facilities may be higher than previously reported, in line with previous research in this area,4 28 30 33 34 the quality of ACP practices would be highly variable.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…This paper presents the key findings of the pre-implementation evaluation; post-implementation changes to these findings will be reported in a future paper. We hypothesised that although pre-implementation ACP awareness and practice within the project facilities may be higher than previously reported, in line with previous research in this area,4 28 30 33 34 the quality of ACP practices would be highly variable.…”
supporting
confidence: 63%
“…The legislation varies in terminology, intent and associated physician liability 27 28. A number of studies have examined aspects of ACP in Australia, including guidelines for implementing ACP in Australian healthcare settings,1 4 29 30 the roles of different health practitioners in supporting ACP,31–34 and the outcomes of a randomised controlled trial in which elderly patients were allocated to receive usual care or facilitated ACP 6. In the specific context of Australian residential aged care facilities (RACFs), development of advance care plans may or may not be part of the institution's policy, and in those settings where the importance of the ACP process is recognised, the quality of processes and instruments developed has been found to be variable and often questionable 4 28 30 33 34.…”
mentioning
confidence: 99%
“…[41][42][43][44][45] Nair et al 45 surveyed Directors of Care regarding the relative use of formal and informal methods of advanced care planning in 88 residential aged care facilities in the Hunter region of New South Wales. They found low levels of formal methods of advanced care planning; only 0.2% of residents had an advanced directive, 1.1% of residents had no CPR orders documented in their medical records, 5.6% had a formal guardian and 2.8% had an enduring guardian.…”
Section: Advance Care Planningmentioning
confidence: 99%
“…10 Nair et al examined the process of advance care planning and the prevalence of advance directives in 88 residential aged care facilities in New South Wales. 11 Directors of care in the facilities were asked to indicate what formal or informal processes were available for residents' decision-making, including living wills, cardiopulmonary resuscitation (CPR) orders and enduring guardian or a formal guardian appointed by the Guardianship Board. In 10.6% of cases no clear process for medical decision-making was documented in the medical notes.…”
Section: Advance Care Planning In Residential Aged Care Facilitiesmentioning
confidence: 99%
“…These results indicate that while the formal process does not appear to be happening, an informal process is occurring. 11 In the United States (US), there is legislative support for advance directives, yet the majority of competent and incompetent residents lack a clear process for decision-making. Canadian research conducted on the last 48 hours of life of residents dying in longterm care facilities found that advance directives were not found in 67% of charts.…”
Section: Advance Care Planning In Residential Aged Care Facilitiesmentioning
confidence: 99%